Autour des noms des personnes chez les kabyles - Nassima Laddaoui; Hayat Bennadji (Multilinguales)
This article explores the issue of placement of people’s names in kabylian society. People’s names are an essential part of the tribal culture, as they carry meanings and symbols that express the society’s history, values, and traditions. This study examines some habits related to names and their use in the family, the village and the throne. It also deals with some of the factors affecting the choice of names in tribal societies, and sheds light on the internal and external cultural influences that control this choice. People’s names are influenced by the values ​​and concepts of tribal society, including religious beliefs and social traditions. The article also deals with the evolution of people’s names in the tribal society and their changes over time. It turns out that the evolution of names is influenced by factors such as social, cultural and demographic changes. This development may be reflected in the selection of new names or a change in the approved nominal patterns. The article also refers to the importance of people’s names in tribal society and their role in building individual identity and social belonging. People’s names are associated with tribal identity and reflect social and cultural ties in the community. By understanding people’s names and their evolution, we can delve deeper into understanding tribal culture and its coexistence with modern social transformations. In short, this article reflects on the importance of people’s names in tribal societies and explores their development, contributing to a deeper understanding of the culture and social identity in these societies.